Analysis of Yogyakarta Coffee Shop Visitor Reviews to Increase Customer Satisfaction Using Sentiment Analysis - Mawadati, Argaditia; Ustyannie, Windyaning; Hindarto Wibowo, Agus; Adelina Simanjuntak, Risma (KnE Social Sciences, 2024)
Visitor reviews written on Google Reviews can show the quality of a product or business. It can also indirectly be a promotion that attracts new consumers. There is a lot of information that can be processed from Google Review that is useful for improving business quality and customer satisfaction. One method that can be used to analyze review data is sentiment analysis. This study analyzed the reviews of coffee shop visitors in the Yogyakarta area written on Google Rewies using the Naïve Bayes Method. Visitor reviews were analyzed using sentiment analysis to see if visitor reviews tend to be positive or negative. Coffee shop business voters can see the level of customer satisfaction and find out what things need to be maintained and improved to increase customer satisfaction. The results of the sentiment analysis showed that more words were detected as positive than negative. Coffee shop visitors in Yogyakarta showed more positive emotions about their experiences when visiting coffee shops, which means most visitors were satisfied with the services and products offered by coffee shop owners in Yogyakarta. Visitors most often wrote about good coffee, price, friendly, suitable, spacious parking, hanging out, comfort, food, service, taste, and working space. Thus, coffee shop owners should focus on those things to increase their customer satisfaction. Keywords: visitor reviews, Google Reviews, sentiment analysis, customer satisfaction